Second-best Properties of Implicit Social Security Taxes: Theory and Empirical Evidence - Robert Fenge; Silke Uebelmesser; Martin Werding (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper investigates the inter-temporal structure of implicit taxes that arise in unfunded pension schemes. We demonstrate that these tax rates are declining over the life cycle. Using German micro-data for men and married women we estimate periodic wage elasticities of labour supply in order to check the second-best properties of this timing of tax rates. An efficient taxation would require to decrease the excessive implicit taxes for married women and to implement an inversely J-shaped tax profile for male workers. This result contradicts the standard proposal to smooth the profile of implicit tax rates across the individual life cycle
Keywords: 330; public pensions; labour supply; optimal taxation